2010
DOI: 10.1007/s11255-010-9729-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cathepsin D serum concentration and carotid intima-media thickness in hemodialysis patients

Abstract: Based on the results of this study, cathepsin D could be suggested to have a role in the development of atherosclerotic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
4
16
0
1
Order By: Relevance
“…Especially among newly diagnosed type 2 diabetic patients, cathepsin D were strongly correlated with insulin resistance. In agreement with previous finding [ 12 ], our data indicate that circulating cathepsin D levels associate positively with triglyceride levels in all participants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Especially among newly diagnosed type 2 diabetic patients, cathepsin D were strongly correlated with insulin resistance. In agreement with previous finding [ 12 ], our data indicate that circulating cathepsin D levels associate positively with triglyceride levels in all participants.…”
Section: Discussionsupporting
confidence: 93%
“…Although cathepsin D has been implicated in acidic milieu of lysosomes with important consequences in regulation of apoptosis, it represents an important prognostic factor in a variety of cancers and is therefore considered to be a potential important molecule and influences cell signaling [ 10 ]. Previous studies have suggested that cathepsin D plays an important role in cholesterol trafficking and atherosclerosis [ 11 , 12 ]. Cathepsin D has been proposed as a biomarker for nonalcoholic steatohepatitis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have recently reported that plasma CatD was strongly associated with pediatric NASH11. Likewise, a correlation exists between CatD and carotid intima-media thickness, an indicator for atherosclerosis49, as well as with a lysosomal storage disease50, diseases which both are predominantly characterized by chronic systemic inflammation and excessive cholesterol storage inside macrophages. In line, in the current paper, we show that CatD is correlated with histological classifications for NASH as well as with cholesterol.…”
Section: Discussionmentioning
confidence: 94%
“…For examples, decreased myocardial CTSD protein levels in human dilated cardiomyopathy (DCM) and increased plasma levels of CTSD in patients with acute coronary syndrome were reported; 32, 33 furthermore, a higher level of serum CTSD was associated with atherogenesis, 34 increased risk of coronary events, 35 carotid intima-media thickness, 36 and endothelial dysfunction. 37 However, important questions regarding how CTSD deficiency affects cardiac function and whether the altered myocardial CTSD expression plays an important role in cardiac pathogenesis remain unanswered.…”
mentioning
confidence: 99%